Human Rights in Libya : the Impact of International Society Since 1969. - De Bona, Giacomina (Routledge studies in Middle Eastern politics., 2012)
Since the end of the Cold War a democratic wave has swept through large parts of the world, propagating liberal values and giving impetus to the case for human rights in an international society. To date however, the promotion of human rights has presented a mixed account with some countries lagging behind others in terms of their observance. In an effort to account for these differences, this book analyzes the relationship between norms and the social construction of international society, and examines how human rights are promoted in that context. Focussing on Libya as a case study.